THE EFFECT OF BOARD GAME METHOD ON STUDENTS’ WRITING DESCRIPTIVE TEXT SKILL (A study at the Seventh Grade of MTs Darul Akhiroh Marancar in 2020/2021 Academic Year) - asiah rosadi (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract : The purpose of this research are to find out : 1) the extent of application of board game method on students’ writing descriptive text skill at the seventh grade of MTs Darul Akhiroh Marancar. 2) the extant of the students’ writing descriptive text skill before and after using board game method on students’ writing descriptive text skill at the seventh grade of MTs Darul Akhiroh Marancar, 3) whether there is any significant effect of board game method on students’ writing descriptive text skill at the seventh grade of MTs Darul Akhiroh Marancar. The population of this research all of the sevenht grade of MTs Darul Akhiroh Marancar consist of 27 students. The sample was 27 students which are taken by total sampling. The research method is used by experimental method. Then, the data collected by using the observation sheet and test. The instrument used is essay. The calculation of t-test formula is higher than score of t-table. The score of t test is 2.2 meanwhile the score of t table is 2,06 at 5 % significant level with (df) 26. And the hypothesis is accepted. It means that there is a significant effect of board game method on students’ writing descriptive text skill at the seventh grade of MTs Darul Akhiroh Marancar in 2020/2021 academic year. Keywords: Board Game, Writing Descriptive Abstrak : Tujuan dari penelitian ini adalah untuk mengetahui : 1) penarapan board game method dalam penulisan descriptive siswa kelas VII MTs Darul Akhiroh Marancar, 2) mengetahui sebelum dan sesudah penggunaan board game method dalam penulisan descriptive siswa kelas VII MTs Darul Akhiroh Marancar, mengetahui apakah ada pengaruh yang signifikan dari board game method terhadap penguasaan penulisan siswa kelas VII MTs Darul Akhiroh Marancar Tahun Akademik 2020/2021. Populasi pada penelitian ini adalah seluruh siswa kelas VII MTs Darul Akhiroh Marancar yang terdiri dari 27, teknik sampling yang digunakan adalah total sampling dengan jumlah 27 siswa. Metode penelitian digunakan adalah ekperimental method. Pengumpulan data menggunakan observation sheet dan tes sebagai instrument. Nilai rata-rata dari penerapan board game method adalah 3.6, dengan kategori “ Sangat Baik”. peneliti menganalisis data menggunakan ttest formula, hasil ttest = 2.2 sedangkan ttable = 2.06. Dengan kata lain ttest lebih besar dari ttable. Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan dari board game method dalam penguasaan penulisan siswa pada kelas VII MTs Darul Akhiroh Marancar. Kata Kunci : Board Game, Writing Descriptive